The secreted FoAPY1 peptidase promotes Fusarium oxysporum invasion - Qian, Hengwei; Song, Limin; Wang, Lulu; Wang, Baoshan; Liang, Wenxing (Frontiers in Microbiology, 2022)
The secretion of peptidases from several pathogens has been reported, but the biological function of these proteins in plant-pathogen interactions is poorly understood. Fusarium oxysporum, a soil-borne plant pathogenic fungus that causes Fusarium wilt in its host, can secrete proteins into host plant cells during the infection process to interfere with the host plant defence response and promote disease occurrence. In this study, we identified a peptidase, FoAPY1, could be secreted from F. oxysporum depending on the N-terminal signal peptide of the protein. FoAPY1 belongs to the peptidase M28 family and exerts peptidase activity in vitro. Furthermore, the FoAYP1 gene knockout strain (∆FoAYP1) presented reduced virulence to tomato plants, but its mycelial growth and conidiation were unchanged. Moreover, FoAYP1 overexpression tomato seedlings exhibited enhanced susceptibility to F. oxysporum and Botrytis cinerea strains. These data demonstrated that FoAYP1 contributes to the virulence of F. oxysporum may through peptidase activity against host plant proteins.